Understanding and mitigating cascading crises in the global interconnected system. (September 2018) - Pescaroli, Gianluca; Nones, Michael; Galbusera, Luca; Alexander, David
Abstract: Cascading crises and disasters in the global interconnected system are emerging topics in today's disaster risk reduction research. The primary objective is improving the capability of our societies to cope with such events and mitigate their detrimental consequences through an evolved understanding of their nature. Rather than being merely considered as an outcome of low-probability/high-impact processes, cascading events can be associated with the cross-scale accumulation of vulnerability paths constituted by events waiting to happen. In this context, instead of focusing solely on triggering events, it seems important to point out the interactions orienting the escalation of secondary emergencies through vulnerability paths. This special issue integrates those emerging aspects with an operational approach that considers cascades as the complex, non-linear escalation of secondary emergencies. Key topics addressed by the contributions include: cross-domain modelling of interdependent systems; decision support systems; economic impact assessment of critical events; and cascades in the built environment, in social domains, and in applied emergency management. Our conclusions support the work of academia, and of public and private stakeholders, by providing a comprehensive analysis of the topic for the improvement of theory, the assessment of resilience, the formulation of policies for managing crises, and operational planning for emergencies. Highlights: Introduction to the SI "Understanding and Mitigating Cascading Crises in the Global Interconnected System". We point out key findings of the papers in terms of theory, methodology and organisational steps for understanding and mitigating cascading crises. The conclusions highlight new areas for integrated and collaborative research that involves cascading risk.